Kaliwete feasibility study - Boto, Danielle Ivy; Ranay, Alyssa Hedwig; Singson, John Michael; Tuazon, Diane
Online shopping in the Philippines is a rapidly growing trend, and it was estimated that 30% of the population use the internet. Moreover, roughly 13% of the population is left-handed. Presently, left-handed people are not aware of their need for and advantages of left-handed items. Because of this, KALIWETE, an upcoming online trading company aims to provide superior quality and ergonomic items to left-handed people living in the Philippines. The online shop will offer them a wide array of left-handed products ranging from scissors, kitchen implements,tools, and school supplies. These people will be assured of high quality yet competitive prices by tight partnerships with suppliers here and abroad, and secure and safe shopping via the online shop, kaliuiete.com.ph. Although there are already existing international sites that offer similar products KALIWETE offers, the company boasts its faster delivery and assured customer service through its real-time tracking of goods and establishment of localized online community for its customers. All our products will be posted on our website, maintained and operated by a hired technical specialist. The owners and operators of the company are all competent graduating BS Industrial Engineering students of the University of the Philippines Diliman. In years two and three, the company will become more profitable as it becomes more popular and increase its clientele. On the next two years, the company plans to expand its business to a brick-and-mortar shop with a wider product range and will create a more interactive community for the left-handed people, the KALIWETE KLUB. KALIWETE will assure to make its customers experience a left-handed-friendly world, that's why the the company lives by its tagline: "Making left the right choice."